2021
DOI: 10.3390/jcm10194539
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Early-Onset Sepsis Is Equally Valid to Culture-Proven Sepsis in Predicting Outcome in Infants after Preterm Rupture of Membranes

Abstract: Background: Culture-proven sepsis is the gold standard in early-onset neonatal sepsis diagnosis. Infants born ≤29 weeks gestation after preterm rupture of membranes in the years 2009–2015 were included in a retrospective cohort study performed at a level III fetal-maternal unit. The study aimed to compare culture-proven sepsis, clinical sepsis and positive laboratory biomarkers ≤72 h as predictors of mortality before discharge and the combined outcome of mortality or severe short-term morbidity (severe cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In cases where infection has finally resulted in preterm rupture of membranes and subsequent preterm birth, culture-proven sepsis is currently considered the gold standard for the diagnosis of early-onset neonatal sepsis. As part of this Special Issue, Grill et al [3] have evaluated their data by comparing culture-proven sepsis, clinical sepsis, and positive laboratory biomarkers as predictors of neonatal mortality. They found that clinical sepsis was almost four times more common than culture-proven sepsis and exhibited similar prediction ability for neonatal mortality and severe morbidity as culture-proven sepsis.…”
mentioning
confidence: 99%
“…In cases where infection has finally resulted in preterm rupture of membranes and subsequent preterm birth, culture-proven sepsis is currently considered the gold standard for the diagnosis of early-onset neonatal sepsis. As part of this Special Issue, Grill et al [3] have evaluated their data by comparing culture-proven sepsis, clinical sepsis, and positive laboratory biomarkers as predictors of neonatal mortality. They found that clinical sepsis was almost four times more common than culture-proven sepsis and exhibited similar prediction ability for neonatal mortality and severe morbidity as culture-proven sepsis.…”
mentioning
confidence: 99%